2015
DOI: 10.1371/journal.pntd.0004255
|View full text |Cite
|
Sign up to set email alerts
|

Cissampelos pareira Linn: Natural Source of Potent Antiviral Activity against All Four Dengue Virus Serotypes

Abstract: BackgroundDengue, a mosquito-borne viral disease, poses a significant global public health risk. In tropical countries such as India where periodic dengue outbreaks can be correlated to the high prevalence of the mosquito vector, circulation of all four dengue viruses (DENVs) and the high population density, a drug for dengue is being increasingly recognized as an unmet public health need.Methodology/Principal findingsUsing the knowledge of traditional Indian medicine, Ayurveda, we developed a systematic bioas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 27 publications
0
67
0
Order By: Relevance
“…Recent estimates show that there are about 400 million infections of dengue fever annually around the world (Sood et al 2015). According to the WHO world malaria report, there are still 214 million new infections worldwide in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates show that there are about 400 million infections of dengue fever annually around the world (Sood et al 2015). According to the WHO world malaria report, there are still 214 million new infections worldwide in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, kaempferol and/or its glycosides were also reported from more than 400 plant species and showed potent antioxidant, anti-inflammatory, antitumor and antimicrobial activities [15]. In conclusion, three compounds, amentoflavone [1], kaempferol 3-O--D-glucopyranoside [2] and kaempferol 3-O--D-glucuronopyranoside [3] were isolated from the aerial parts of C. pareira. These compounds can be utilized as chemotaxonomic markers for the identification of crude drugs based on the aerial parts of C. pareira.…”
Section: Resultsmentioning
confidence: 97%
“…The roots are used for the treatment of indigestion, constipation, cough and cold and applied locally in snake bite [1]. Previous studies have reported antiviral [2], antiprotozoal [3] and antifertility [4] activities of the extracts of aerial parts of C. pareira. Regarding chemical constituents, alkaloids are reported as major constituents in leaves [5] and roots [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several plants have been reported to display antiviral activities [26,27,28,29]. More recently, these medicinal products are described as antiviral agents against DENV, inhibiting the viral load and/or their replication [30,31,32]. …”
Section: Introductionmentioning
confidence: 99%